Ascorbic acid and calcitriol as alternative preventive strategies for myocardial damage in type 2 diabetes mellitus: an in vivo study using diabetic and atherosclerotic rat models - Saputra, Jefri Dwi; Heriansyah, Teuku; Sofyan, Hamny; Dimiati, Herlina; Mudatsir, Mudatsir (Universitas Brawijaya, 2025)
BACKGROUND: Type 2 diabetes mellitus can increase the production of reactive oxygen species (ROS) and genetic transcription factors, such as nuclear factor kappa beta (NF-κB). These phenomena may enhance the progression of atherosclerosis. Additionally, NF-κB can induce apoptosis of pancreatic beta cells and accelerate disease progression. OBJECTIVE: To investigate the role of calcitriol and ascorbic acid on NF-κβ expression in vivo in aortic and myocardial tissues of Wistar rats. METHODS: This randomized experimental study involved 24 male Wistar rats of the Rattus norvegicus strain, divided into four groups: NC (negative control), PC (positive control), AG (ascorbic acid group), and CG (calcitriol group). The study spanned 90 days, including a 30-day intervention period. Aortic and myocardial samples were processed into histological preparations and stained using immunohistochemical techniques. NF-κB expression was assessed using an intensity scoring method. RESULTS: The CG group demonstrated the lowest NF-κB immunoexpression in myocardial tissue (0.27 ± 0.08), followed by the AG (0.37 ± 0.05), NC (0.68 ± 0.08), and PC (1.13 ± 0.34) groups, with statistically significant 3sbetween the groups (p < 0.05). In aortic tissue, the CG group also exhibited the lowest NF-κB expression (0.30 ± 0.18), followed by the AG (0.50 ± 0.09), NC (0.97 ± 0.05), and PC (1.23 ± 0.38) groups, with statistically significant differences between the groups (p < 0.05). Similar trends were observed in the immunohistochemical staining of the NF-κB antigen in myocardial and aortic tissue samples. Calcitriol administration was more effective than ascorbic acid in reducing NF-κB expression in both myocardial (p < 0.05) and aortic tissues (p < 0.05). CONCLUSION: Both ascorbic acid and calcitriol reduce NF-κB expression in the aorta and myocardium, with calcitriol showing greater effectiveness than ascorbic acid.